Toxoplasma encephalitis in congenic B10 and BALB mice: impact of genetic factors on the immune response. - Deckert-Schlüter, M (1994)
Factors which determine the pathogenesis and course of Toxoplasma encephalitis are poorly understood. In the present study, the influence of genetic factors in congenic B10 and BALB mice of H-2q, H-2k, and H-2b haplotypes was examined following oral infection with a low-virulence strain of Toxoplasma gondii (DX). There were striking differences among these strains. Whereas B10 mice were highly susceptible, BALB mice had a less severe and more protracted disease. In all animals with a fatal outcome, Toxoplasma encephalitis was the cause of death. Within the two congenic groups, the major histocompatibility complex haplotype had a strong impact on the disease. The H-2k haplotype was associated with early death in B10 mice but with a favorable outcome in BALB mice, whereas the reverse was observed for the H-2q haplotype. These findings indicate that genetically determined factors are critically involved in determining the intracerebral immune response and the course of murine toxoplasmosis. Some of these factors appear to be associated with the major histocompatibility complex haplotype, but significant differences between B10 and BALB mice point to a modulating role of additional genetic loci. Immunohistochemical studies and cytokine analyses of cerebrospinal fluid and serum revealed significant differences in the intracerebral immune response between susceptible and resistant strains. A poor outcome was associated with a large number of intracerebral parasites, significant tissue necrosis, a reduced number of intracerebral CD4+ T cells, low intrathecal tumor necrosis factor levels, and, to a lesser extent, a reduced number of intracerebral CD8+ T cells.